The quality of Malaysian clinical practice guidelines and relevance to the care of older people / Nadzihah Mohd Nawi ... [et al.] - Mohd Nawi, Nadzihah; Gnanasan, Shubashini; Abd Wahab, Mohd Shahezwan; Karuppannan, Mahmathi (Faculty of Pharmacy, 2020)
Clinical Practice Guidelines (CPGs) are key instruments in providing the most appropriate decision in the treatment of any disease. CPG was developed to improve health care by increasing the incorporation of evidence-based treatments to reduce the use of unnecessary, ineffective or harmful interventions. This study assessed 5 Malaysian CPGs using Appraisal of Guidelines Research and Evaluation II (AGREE-II) instrument which could help the stakeholders to decide if further improvement or modification is needed. AGREE-II is an international instrument that aids in CPG development. It comprises of 23-items under 6 different domains. The κ statistics was used to look for agreement between 3 appraisers across these domains. The relevance of the Malaysian CPG to the care of older people in this study was also assessed using an instrument that have been developed by a previous study (Quality of Australian clinical guidelines and relevance to the care of older people with multiple comorbid conditions). This instrument evaluated if the guidelines addressed the treatment for older people, the burdens to the patients and caregivers as well as patient-centered aspects such as patients' preferences and their quality of life. This study showed that all 5 Malaysian CPGs are of good quality and acceptable to clinical settings according to the AGREE instrument. However, it was found that none of the CPG considered patients' preferences in developing CPGs. In terms of the CPGs' relevance to the care of older people, our results showed that there is poor relevance on the patients' burden of treatment. Only two CPGs (Management of Type 2 Diabetes Mellitus and Management of Hypertension) had a higher agreement between the appraisers compared to other CPGs in relation to management of medical conditions in older patients. As a conclusion it was found all 5 Malaysian CPGs evaluated were in good quality but need improvement in terms of involving stakeholder in the development of CPGs at par with other developed countries.